Endodontic treatment of the lower left deciduous second molar in a patient with oligodontia - case report (Research, Society and Development, 2022)
The present article is a case study, with a descriptive and qualitative structure, in order to report endodontic treatment in a left deciduous second molar (75) in a patient with oligodontia is reported. After anamnesis and clinical examination, the diagnosis of pulp necrosis was established. Subsequently, the carious tissue was removed with a spherical bur at low speed, the element was isolated, accessed and the chemical-mechanical preparation was carried out with the aid of rotary nickel-titanium files of the Sequence BabyFile system, 2.5% sodium hypochlorite and 17% ethylenediaminetetraacetic acid, using stirring protocol. The filling of the root canal system was performed with iodoformed calcium hydroxide paste, inserted with a lentulo spiral. Patients with oligodontia require multidisciplinary follow-up and endodontic treatment of deciduous teeth, especially when necrotic, avoids early extractions and, in the absence of a permanent successor, has great value in the treatment plan, aiming at maintaining space and alveolar bone, anchoring orthodontic devices and prevent extrusion of antagonistic elements.